2023
DOI: 10.1371/journal.pone.0291942
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of evolutionary dynamics for drug resistance in 3D spheroid model system using cellular barcoding technology

Gizem Damla Yalcin,
Kubra Celikbas Yilmaz,
Tugce Dilber
et al.

Abstract: Complex evolutionary dynamics governing the drug resistance is one of the major challenges in cancer treatment. Understanding these mechanisms requires a sequencing technology with higher resolution to delineate whether pre-existing or de novo drug mechanisms are behind the drug resistance. Combining this technology with clinically very relevant model system, namely 3D spheroids, better mimicking tumorigenesis and drug resistance have so far been lacking. Thus, we sought to establish dabrafenib and irinotecan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Intertumoral and intratumoral heterogeneity have been a hot topic of research in the past years ( Liu et al, 2018 ; Bergmann et al, 2020 ; Yalcin et al, 2020 ; Grzywa et al, 2021 ). The tumor heterogeneity contributing to the presence of one or more cancer cell clones that are resistant to the chemotherapeutic agent of choice could be present prior to the treatment or it might emerge during the course of the treatment ( Kelderman et al, 2014 ; Danisik, et al, 2023 ; Yalcin et al, 2023 ; Baygin et al, 2024 ). The heterogeneous nature of the tumor population contributes to the latter; acquired therapeutic resistance and poses a serious threat to the therapeutic outcomes ( Foo and Michor, 2014 ; Acar et al, 2020 ).…”
Section: Metronomic Chemotherapy: Mechanisms Of Actionmentioning
confidence: 99%
“…Intertumoral and intratumoral heterogeneity have been a hot topic of research in the past years ( Liu et al, 2018 ; Bergmann et al, 2020 ; Yalcin et al, 2020 ; Grzywa et al, 2021 ). The tumor heterogeneity contributing to the presence of one or more cancer cell clones that are resistant to the chemotherapeutic agent of choice could be present prior to the treatment or it might emerge during the course of the treatment ( Kelderman et al, 2014 ; Danisik, et al, 2023 ; Yalcin et al, 2023 ; Baygin et al, 2024 ). The heterogeneous nature of the tumor population contributes to the latter; acquired therapeutic resistance and poses a serious threat to the therapeutic outcomes ( Foo and Michor, 2014 ; Acar et al, 2020 ).…”
Section: Metronomic Chemotherapy: Mechanisms Of Actionmentioning
confidence: 99%
“…In particular, Szczepanik et al recently demonstrated that AST addition is able to reduce free radicals and protect porcine cells from oxidative damage [ 30 ]. The molecular mechanisms involved in these beneficial effects are under elucidation and, for this purpose, commercially available human (Caco-2 and HT-29) as well as pig (IPEC-J2) cell lines have been used to develop in vitro models [ 31 , 32 , 33 , 34 , 35 , 36 ]. In addition, all these studies have been performed using in vitro 2D culture systems that only partially reflect the complexity of the intestinal barrier.…”
Section: Introductionmentioning
confidence: 99%